Major determinants and possible mechanism of dobutamine-induced left ventricular outflow tract obstruction in patients with a sigmoid ventricular septum - Tano, Ayako; Kasamaki, Yuji; Okumura, Yasuo; Ohta, Masakatsu; Kofune, Tatsuya; Fujii, Nobuyuki; Aizawa, Yosihiro; Nakai, Toshiko; Kunimoto, Satoshi; Hiro, Takafumi; Watanabe, Ichiro; Hirayama, Atsushi (Journal of cardiology, 2013)
A sigmoid ventricular septum (SVS) may be related to normal aging, but some people with an SVS develop a left ventricular outflow tract (LVOT) obstruction (defined as a gradient of >30mmHg). Therefore, we investigated the association of LVOT obstructions with an SVS by dobutamine stress echocardiography (DSE) and assessed the possible mechanism of the latent LVOT obstruction. DSE was performed in 64 subjects with SVS (mean age: 73.3±7.7 years; 36 women) without an LVOT obstruction. In 40 of the 64 subjects, an LVOT obstruction occurred during the DSE (defined as latent obstruction). At rest, the subjects with a latent obstruction had a shorter end-systolic mitral leaflet tethering distance (“α” distance, i.e. the distance between the tip of the posterior papillary muscle and the contralateral anterior mitral annulus) than those without one (29.9±4.2mm versus 35.2±4.6mm), as well as a smaller end-systolic LVOT diameter (13.4±2.7mm versus 16.1±3.4mm) and larger ejection fraction (72.0±5.0% versus 67.8±5.9%) (all p<0.05). They also had a higher LV outflow velocity at rest (1.23±0.24m/s versus 1.03±0.24m/s) and during the Valsalva maneuver (1.31±0.27m/s versus 1.03±0.27m/s) (both p<0.05). After adjusting for these parameters, the resting end-systolic “α” distance and LV outflow velocity at rest remained independent predictors of a latent obstruction. A short leaflet tethering distance (“α”) was the major determinant of a latent obstruction, suggesting that a mitral leaflet displacement/redundancy caused by a short “α” distance contributes to the LVOT obstruction.